China–Pakistan Relations (1999–2025): Strategic Convergence, Economic Dependencies, and Security Challenges - Sanam Latif; Dr. Noor Hamid Khan (Social Science Review Archives, 2025)
This research paper critically examines the multifaceted dimensions of the Pakistan–China relationship with a particular focus on the Belt and Road Initiative (BRI) and the China–Pakistan Economic Corridor (CPEC). Through historical, economic, security, socio-cultural, and theoretical lenses, it evaluates how bilateral cooperation has evolved, where it has succeeded, and where vulnerabilities persist. Drawing upon recent data (2022–2025) and comparative analysis with other BRI cases, the study highlights both structural asymmetries and opportunities. While infrastructure expansion, trade facilitation, educational linkages, and cultural diplomacy have strengthened Pakistan’s integration with China, persistent financing challenges, security threats, governance limitations, and public skepticism dilute the long-term sustainability of the partnership. Findings reveal that while Pakistan’s overdependence on China constrains strategic autonomy, CPEC nonetheless provides a transformative platform that, if managed with transparency and inclusivity, can mitigate structural imbalances. The paper concludes with policy recommendations for institutional strengthening, diversification of cooperation beyond CPEC, and proactive regional diplomacy to ensure a balanced, sustainable, and people-centered partnership.